Estudo da oxidação de sulfetos pró-quirais com oxo diperoxo complexos de molibdênio (VI) - Simões, Bianca Rebelo Lopes (Universidade Federal de São Carlos, 2007)
This study describes the use of oxo diperoxo molybdenum (VI) complex using 2,2-bipyridine and N,N -dioxide-2,2 -bipyridine as ligands for the oxidation of a series of aliphatic and aromatic sulfides, ketosulfides, sulfinyl acids and olefinic sulfides. The preparation of these complexes, the reactivity and the chemeoselectivity in these sulfides oxidation reactions are discussed. This work also describes the enantioselectivity results obtained for the oxidation reaction of a series of alkyl aryl prochiral sulfides using the MoO5(N,N-DMLA) chiral complex. The enantioresolution of the series of alkyl aryl sulfoxides, using chiral polysaccharide stationary phases, in multimodal elution, is also demonstrated. The reactivity of MoO5(pyridine oxide)(H2O) complex, coated and uncoated to silica gel, for the series of alkyl aryl sulfides oxidation reactions were also thoroughly evaluated for comparison with the results obtained in previous studies with a different series of sulfide. The result obtained in this work discloses that, in these oxidation, reactions the reactivity depends, not only of the used complex, but also, of the nucleophilicity of the used sulfides. The preparation of MoO5(N,N-DMLA) chiral complex, by a variety of methods, and the characterization of the obtained products by infrared, ultraviolet 13C-NMR, microanalyses and optical activity are also reported.
Oxidation study of prochiral sulfides with oxo diperoxo Molybdenum (vi) complexes
Keywords: Síntese orgânica; Oxidação; Sulfóxidos quirais; Sulfetos pró-quirais; Peroxo complexos de molibdênio; CIENCIAS EXATAS E DA TERRA::QUIMICA